“Evaluación del Síndrome Metabólico a los Estudiantes de secundaria de la I.E. 80818 “Jorge Basadre Grohmann” Florencia de Mora, 2016” - Arce Negreiros, Denis Fabiola (2017)
The metabolic syndrome (MS) is one of the greatest public health problems of our time, since it favors the increase of cardiovascular diseases, arterial hypertension and type 2 diabetes; Therefore, the objective of the present study is to determine the presence of MS in high school students of the I.E. 80818 "Jorge Basadre Grohmann" Florence de Mora, 2016. The population sample consisted of 130 students (chosen by random stratified sampling). Anthropometric tests (weight, height, BMI), blood pressure measurement and biochemical tests were performed to determine serum levels of glucose, triglycerides, cholesterol, HDL, VLDL, LDL, cholesterol / HDL ratio, prior consent and assent Informed by parents and students respectively. The experimental work was carried out in the Laboratory of Biological Analysis "Cartavio". From the evaluation it was found that 11.54% of the total population had MS, whereas 6.92% were obese, 21.54% had hypertension, 10.77% had hyperglycemia, 32.31% had hypercholesterolemia and 27.69% had hypertriglyceridemia. Also, more than half of second grade students (55.55%) presented hypercholesterolemia and 37.04%, hypertriglyceridemia; As well as 14.81% have obesity, and the highest percentage of students with hypertension are fourth grade (33.33%); Higher percentages compared to the other grades. It was concluded that the MS, probably due to the students of the first grades present a lifestyle in their diet rich in fats, carbohydrates and sweets; Which has generated the high values obtained in obesity and overweight, the opposite is observed in the fourth and fifth grades, these present a lower percentage of obesity, but high values of arterial hypertension.